SMEs and internationalization: an empirical study of SMEs in Portugal - Trigo, V.; Calapez, T.; Santos, M. C. (Economia Global e Gestão, 2009)
This paper presents the results of a survey of small and medium-sized enterprises (SMEs) in Portugal drawn from a database of 2500 SMEs supplied by COFACE – the holder of the largest company database in Portugal. It is an exploratory study presenting descriptive results on their export drive, competitiveness in external markets, analysis of the environment, and innovation concerns vis-à-vis global markets and information needs for these markets. We draw from recent literature to identify the main features global markets require of companies if they are to operate successfully and compare them with our findings. Portugal was selected as the basis of our study not only because local companies have faced great changes in the last three decades following the transition from a closed and protected economy to full membership within the European Union and the current very open economy, but also because the country and population are so small that companies face tremendous pressures to internationalize as the domestic market for many types of goods is very limited.